Leadership in Learning Networks: How can conveners use networked learning perspectives in convening people and learning networks? - Boerma, Sebo; Coenders, Marc; Veeneman-Aukema, Anna; Luimstra, Simon Henk (Proceedings of the International Conference on Networked Learning, 2018)
In this workshop we introduce the social discipline of learning, we investigate the relational part of learning networks and in that light want to discuss the way conveners can play a role in improving these learning networks. We are especially interested in the way networked learning can be used for convening learning networks. We will present cases of recent research we performed or are performing on influences of elements of learning networks, especially the common knowledge agenda and the identity of the network. Next to that we will present research we performed and are performing on the role conveners play in these networks.